Aberrantly up-regulated miR-142-3p inhibited the proliferation and invasion of trophoblast cells by regulating FOXM1. (15th January 2021) - Mao, Yan; Hou, Bin; Shan, Long; Sun, Xiaotong; Wang, Li
Abstract: Introduction: Preeclampsia is one of the main causes of morbidity and mortality in pregnant women and mothers. Numerous studies showed that microRNAs (miRNAs) played important roles in the occurrence and development of preeclampsia. However, the regulation of microRNA-142-3p (miR-142-3p) in preeclampsia has not been clarified. Methods: The expression of miR-142-3p and FOXM1 was detected by RT-qPCR. The interaction between miR-142-3p and FOXM1 was confirmed by dual-luciferase reporter assay. The relative protein expression of FOXM1 was measured by western blot. Cell proliferation was measured using MTT assay. Cell migration was detected using transwell assay and wound healing assay. Results: The expression of miR-142-3p was up-regulated, while the mRNA and protein of FOXM1 expression were down-regulated in preeclampsia tissues. Additionally, we found that miR-142-3p targeted FOXM1. Moreover, FOXM1 expression was negatively regulated by miR-142-3p. Functional experiments showed that overexpression of miR-142-3p inhibited cell growth and migration in trophoblast cells. Reverse experiments determined that overexpression of FOXM1 reversed the suppressive effects of miR-142-3p on cell proliferation and migration. Discussion: Our results demonstrated that miR-142-3p regulated cell proliferation and migration through targeting FOXM1 in trophoblast cells, providing a novel therapeutic target and extending the pathogenesis of preeclampsia. Highlights: The expression of forkhead box protein M1 (FOXM1) and miR-142-3p in human preeclampsia (PE) placenta tissues. MiR-142-3p regulates forkhead box protein M1 (FOXM1) expression in trophoblast cell lines. MiR-142-3p regulates the cell growth and migration in trophoblast cells. Effects of FOXM1 downregulating and upregulating on cell growth and migration in trophoblast cells. miR-142-3p inhibits trophoblast cell growth and migration by targeting FOXM1 in trophoblast cells.